Alloy catalyst and preparation method thereof
By using a core-shell alloy catalyst in a fuel cell, an oxidation treatment and annealing treatment are carried out in an atmosphere containing oxygen and carbon monoxide, a carbon-clad alloy catalyst with a highly ordered structure is formed, which solves the problem of poor durability caused by instability of transition metal elements, and achieves high activity and long durability.
Patent Information
- Application Number
- CN202411974013.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
During the durability process, the transition metal elements of existing alloy catalysts are unstable and easily dissolved, resulting in reduced catalytic activity and poor durability.
The preparation method of core-shell alloy catalyst is adopted, and the oxidation treatment and annealing treatment are carried out in an atmosphere containing oxygen and carbon monoxide to form a carbon-clad alloy catalyst with a highly ordered structure to inhibit the agglomeration, dissolution and fall off of alloy nanoparticles.
The high activity and long durability of the alloy catalyst are achieved, the catalytic and durable properties are improved, the preparation process is simplified, and mass production is easy.
Smart Images

Figure CN119764467A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to an alloy catalyst and a preparation method thereof. Background Art
[0002] In order to achieve widespread commercialization of proton exchange membrane fuel cell (PEMFC) technology, it is necessary to improve the activity of catalysts and reduce costs. In PEMFC, the slow rate of oxygen reduction reaction (ORR) leads to large overpotential at low temperature. Therefore, it is crucial to develop highly active cathode electrocatalysts. In order to achieve high activity for ORR, it is important to uniformly disperse and control the particle size of Pt. Pt particle agglomeration leads to a reduction in the surface area of the electrocatalyst and a continuous decrease in catalytic activity. In order to obtain high-quality and active Pt, various binary and ternary Pt-based alloy catalysts on high-surface-area supports have been reported. Compared with Pt / C, Pt alloy / C (such as PtCo, PtNi, etc.) has 2-4 times higher ORR activity in PEMFC. However, due to the unstable nature of the transition metal elements in the alloy catalyst, it is very easy to dissolve from the metal nanoparticles during the durability process, resulting in poor durability. Ordered alloy catalysts have high durability due to their unique structure, but the formation of the ordered structure of the alloy requires higher temperatures, which causes the alloy nanoparticles to agglomerate and grow, affecting the active sites of the alloy catalyst, resulting in low ORR activity. Core-shell alloy catalysts have high ORR activity and high durability, but the formation of the platinum shell usually requires acid washing and secondary heat treatment, which involves many steps and the process is cumbersome and difficult to control. Summary of the invention
[0003] The present application provides an alloy catalyst and a preparation method thereof, which have high catalytic performance and long durability.
[0004] The embodiment of the present application is implemented as follows:
[0005] In a first aspect, the present application provides an example of a method for preparing an alloy catalyst, comprising:
[0006] The initial alloy catalyst is placed in an atmosphere containing oxygen for oxidation treatment to obtain a first precursor, and then the first precursor is placed in an atmosphere containing carbon monoxide for annealing treatment. The annealing temperature is 650°C to 900°C, and the annealing time is 2h to 5h to obtain an alloy catalyst, wherein the initial alloy catalyst includes a carrier and initial alloy particles loaded on the carrier, and the initial alloy particles include platinum and a transition metal.
[0007] In the above technical solution, the initial alloy catalyst is first oxidized in an atmosphere containing oxygen so that the transition metal is fully oxidized, and then the first precursor is annealed in an atmosphere containing carbon monoxide. The carbon monoxide gas can not only induce platinum segregation, thereby forming the outermost platinum shell of the alloy nanoparticles, but also reduce the transition metal oxide to form oxygen vacancies, accelerate the diffusion of transition metal elements, promote the formation of ordered structures, and improve the order of the alloy nanoparticles. In addition, the carbon monoxide gas will form a carbon layer in the reaction process with the transition metal oxide. The carbon layer is physically coated on the surface of the alloy nanoparticles to limit the growth of the alloy nanoparticles, and finally obtain an ordered core-shell alloy catalyst with smaller particles and uniform distribution.
[0008] The preparation method of the core-shell alloy catalyst of the present application is simpler and easier to mass produce than the conventional pickling and secondary heat treatment, and a carbon-coated alloy catalyst is synthesized which has the effect of inhibiting the agglomeration, dissolution and shedding of alloy nanoparticles. The prepared alloy catalyst not only has a highly ordered core-shell structure which can effectively inhibit the dissolution of base metals, but also has better catalytic performance and durability than uncoated catalysts, truly achieving both high catalytic performance and long durability.
[0009] In some possible embodiments, the molar ratio of platinum to transition metal in the initial alloy particles is 1:3 to 5:1; and / or the support comprises a carbon support or an oxide support.
[0010] In some possible implementation schemes, the atmosphere of the annealing treatment includes carbon monoxide and an inert gas, and the volume ratio of carbon monoxide to the inert gas is 10 mL:200 mL to 100 mL:300 mL.
[0011] In the above technical solution, by making the volume ratio of carbon monoxide and inert gas within the above range, it is beneficial for carbon monoxide gas to induce platinum segregation, thereby forming the outermost platinum shell of the alloy nanoparticles outward, and at the same time reducing the transition metal oxide to form oxygen vacancies to accelerate the diffusion of transition metal elements and promote the formation of ordered structures, thereby improving the order of the alloy nanoparticles. In addition, carbon monoxide gas forms a carbon layer during the reaction process with the transition metal oxide, and the carbon layer is physically coated on the surface of the alloy nanoparticles to limit the growth of the alloy nanoparticles, and finally an ordered core-shell alloy catalyst with smaller particles and uniform distribution is obtained.
[0012] In some possible implementation schemes, the temperature of the oxidation treatment is 80° C. to 100° C., and the time of the oxidation treatment is 2 h to 5 h.
[0013] In the above technical solution, by making the temperature and time of the oxidation treatment within the above range, it is beneficial to control the size of the alloy nanoparticles and at the same time make the transition metal fully oxidized.
[0014] In some possible embodiments, the atmosphere for the oxidation treatment is air.
[0015] In some possible embodiments, the initial alloy catalyst can be prepared by the following method: placing the freeze-dried material in an atmosphere containing hydrogen for heat treatment, the heat treatment temperature is 200°C to 400°C, and the heat treatment time is 2h to 5h; the freeze-dried material includes a mixture of a transition metal precursor, a platinum precursor and a carrier.
[0016] In the above technical solution, a freeze-dried product of a mixture including a transition metal precursor, a platinum precursor and a carrier is heat-treated in an atmosphere containing hydrogen, so that the transition metal precursor and the platinum precursor are reduced to transition metal and platinum, respectively, to form an alloy of transition metal and platinum. In other possible embodiments, the initial alloy catalyst can also be prepared by a conventional impregnation method or a colloid method.
[0017] In some possible implementation schemes, the lyophilized material is prepared by the following method: after the transition metal precursor, the platinum precursor and the carrier are mixed, they are transferred to a glass surface dish within 5 minutes for rapid pre-freezing to obtain a pre-frozen material, and then the pre-frozen material is transferred to a freeze dryer for freezing for 18 hours to 30 hours to obtain a lyophilized material.
[0018] In the above technical solution, the mixture is transferred to a glass surface dish within 5 minutes for rapid pre-freezing, so that the mixture including the transition metal precursor, the platinum precursor and the carrier can be locked while maintaining a uniform stirring state, which is beneficial to improving the order of the alloy nanoparticles.
[0019] In some possible embodiments, the transition metal includes any one or more of cobalt, nickel, iron and manganese; and / or the platinum precursor includes any one or more of chloroplatinic acid, platinum acetylacetonate and potassium chloroplatinate.
[0020] In a second aspect, the present application provides an alloy catalyst, which is prepared according to the preparation method of the alloy catalyst in the above embodiment.
[0021] In the above technical scheme, the alloy catalyst of the present application is an ultra-thin carbon layer coated ordered core-shell alloy catalyst, which can inhibit the agglomeration, dissolution and shedding of alloy nanoparticles. It not only has a highly ordered core-shell structure, which can effectively inhibit the dissolution of base metals, but also has better catalytic performance and durability than uncoated catalysts, truly achieving both high catalytic performance and long durability.
[0022] In some possible embodiments, the alloy catalyst includes a carrier and alloy particles loaded on the carrier, the alloy particles include a core, a first shell and a second shell, the first shell is coated on the surface of the core, the second shell is coated on the surface of the first shell, the core is an alloy, the first shell is a platinum layer, and the second shell is a carbon layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 This is a flow chart of a method for preparing an alloy catalyst according to an embodiment of the present application;
[0025] Figure 2 A schematic diagram of the structure of the alloy particles of an embodiment of the present application;
[0026] Figure 3 This is a TEM image of the alloy catalyst prepared in Example 1 of the present application;
[0027] Figure 4 The XRD diagrams of Example 1 and Comparative Example 2 of the present application are shown in FIG.
[0028] Icon: 10-alloy particle; 100-core; 200-first shell; 300-second shell. DETAILED DESCRIPTION
[0029] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] The present application found that in order to improve the unstable characteristics of transition metal elements and the problem of easy dissolution from metal nanoparticles during the durability process, a core-shell catalyst can be used, but the formation of the platinum shell usually requires acid washing and secondary heat treatment, which has many steps and is cumbersome and difficult to control. Overall, there is an urgent need for a preparation method of a core-shell alloy catalyst with controllable metal particle size and high order.
[0031] Based on this, see Figure 1 The present application provides a method for preparing an alloy catalyst, which comprises the following steps:
[0032] S1. Preparation of lyophilized material
[0033] First, the transition metal precursor and the platinum precursor are uniformly mixed in water to obtain a mixed solution, and then the mixed solution and the carrier are added to a mixing tank for mixing. After the mixing treatment is completed, it is transferred to a glass surface dish within 5 minutes for rapid pre-freezing to obtain a pre-frozen material, and then the pre-frozen material is transferred to a freeze dryer for freezing for 18 hours to 30 hours to obtain a freeze-dried material.
[0034] The transition metal precursor includes a transition metal salt, and the transition metal includes any one or more of cobalt, nickel, iron and manganese.
[0035] For example, when the transition metal element is cobalt, the transition metal precursor includes soluble salts such as cobalt nitrate, cobalt chloride, and cobalt acetate.
[0036] The platinum precursor includes any one or more of chloroplatinic acid, platinum acetylacetonate and potassium chloroplatinate.
[0037] The molar ratio of platinum to transition metal elements in the mixed solution is 1:3 to 5:1.
[0038] As an example, the molar ratio of platinum to the transition metal element in the mixed solution may be 1:5, 1:3, 1:1, 2:5, 2:3, 2:1, 3:5 or 3:1.
[0039] Optionally, the method of uniformly mixing the transition metal precursor and the platinum precursor in water includes ultrasonic dispersion.
[0040] The support includes a carbon support or an oxide support.
[0041] The BET specific surface area of the carbon carrier is ≥400m 2 / g.
[0042] Optionally, the carbon support comprises Ketjen Black and / or BP2000.
[0043] Rapid prefreezing methods include liquid nitrogen prefreezing or low-temperature refrigerator prefreezing.
[0044] Optionally, the rapid pre-freezing method is liquid nitrogen pre-freezing.
[0045] After the transition metal precursor, platinum precursor and carrier are mixed, they are transferred to a glass surface dish within 5 minutes for rapid pre-freezing, which can lock the mixture including the transition metal precursor, platinum precursor and carrier while maintaining a uniform stirring state, which is beneficial to improving the order of the alloy nanoparticles.
[0046] As an example, the freezing time of the pre-frozen material in the freeze dryer can be 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h or 30h.
[0047] S2. Preparation of initial alloy catalyst
[0048] The obtained freeze-dried material is placed in an atmosphere containing hydrogen for heat treatment at a temperature of 200°C to 400°C for a time of 2h to 5h to obtain an initial alloy catalyst, which is an alloy supported on a carbon carrier.
[0049] Optionally, the atmosphere of the heat treatment includes hydrogen and an inert gas, and the volume ratio of the hydrogen to the inert gas is 10 mL:200 mL to 100 mL:300 mL.
[0050] The inert gas includes any one or more of nitrogen, helium, neon, argon and xenon.
[0051] As an example, the heat treatment temperature can be 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, 380°C or 400°C, and the heat treatment time can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h.
[0052] Optionally, before the heat treatment is performed, the air in the container to be heat treated is exhausted by using an inert gas.
[0053] Optionally, before reaching the target temperature of the heat treatment, the heating rate is 10° C. / min to 50° C. / min.
[0054] A freeze-dried product of a mixture including a transition metal precursor, a platinum precursor and a carrier is heat-treated in an atmosphere containing hydrogen, so that the transition metal precursor and the platinum precursor are reduced to a transition metal and platinum, respectively, to form an alloy of the transition metal and platinum.
[0055] In other possible embodiments, the initial alloy catalyst can also be prepared by conventional impregnation method or colloid method.
[0056] It should be noted that the molar ratio of platinum to transition metal elements in the initial alloy particles is the same as the molar ratio of platinum to transition metal elements in the mixed solution, which is also 1:3 to 5:1.
[0057] S3. Preparation of alloy catalyst
[0058] The prepared initial alloy catalyst is placed in an atmosphere containing oxygen for oxidation treatment to obtain a first precursor, and then the first precursor is placed in an atmosphere containing carbon monoxide for annealing treatment. The annealing temperature is 650°C to 900°C, and the annealing time is 2h to 5h to obtain an alloy catalyst.
[0059] Optionally, the atmosphere for the oxidation treatment is air.
[0060] The temperature of the oxidation treatment is 80°C to 100°C, and the time of the oxidation treatment is 2h to 5h.
[0061] As an example, the temperature of the oxidation treatment may be 80° C., 85° C., 90° C., 95° C., or 100° C., and the time of the oxidation treatment may be 2 h, 3 h, 4 h, or 5 h.
[0062] By making the temperature and time of the oxidation treatment within the above range, it is advantageous to control the size of the alloy nanoparticles while allowing the transition metal to be fully oxidized.
[0063] Optionally, before reaching the target temperature of the oxidation treatment, the heating rate is 5°C / min to 10°C / min.
[0064] Optionally, the atmosphere of the annealing treatment includes carbon monoxide and an inert gas, and the volume ratio of carbon monoxide to the inert gas is 10 mL:200 mL to 100 mL:300 mL.
[0065] As an example, the volume ratio of carbon monoxide and inert gas can be 10mL:200mL, 20mL:200mL, 50mL:200mL, 80mL:200mL, 100mL:200mL, 10mL:250mL, 20mL:250mL, 50mL:250mL, 80mL:250mL, 100mL:250mL, 10mL:300mL, 20mL:300mL, 50mL:300mL, 80mL:300mL or 100mL:300mL.
[0066] As an example, the temperature of the annealing treatment may be 650° C., 700° C., 750° C., 800° C., 850° C. or 900° C., and the time of the annealing treatment may be 2 h, 3 h, 4 h or 5 h.
[0067] Optionally, the annealing temperature is 700°C to 900°C.
[0068] Optionally, before the annealing treatment is performed, the air in the container where the annealing treatment is performed is exhausted by using an inert gas.
[0069] Optionally, before reaching the target temperature of the annealing treatment, the heating rate is 10° C. / min to 50° C. / min.
[0070] It should be noted that the raw material initial alloy catalyst in S3 can be prepared through the steps of S1 and S2 of the present application, or can be prepared through a conventional impregnation method or colloid method, or can be directly purchased.
[0071] The preparation method of the alloy catalyst of the present application firstly oxidizes the initial alloy catalyst in an atmosphere containing oxygen, so that the transition metal is fully oxidized, and then the first precursor is annealed in an atmosphere containing carbon monoxide. The carbon monoxide gas can not only induce platinum segregation, thereby forming the outermost platinum shell of the alloy nanoparticles, but also reduce the transition metal oxide to form oxygen vacancies, accelerate the diffusion of transition metal elements, promote the formation of ordered structures, and improve the order of the alloy nanoparticles. In addition, the carbon monoxide gas will form a carbon layer in the reaction process with the transition metal oxide, and the carbon layer will be physically coated on the surface of the alloy nanoparticles to limit the growth of the alloy nanoparticles, and finally obtain an ordered core-shell alloy catalyst with smaller particles and uniform distribution.
[0072] The preparation method of the core-shell alloy catalyst of the present application is simpler and easier to mass produce than the conventional pickling and secondary heat treatment, and a carbon-coated alloy catalyst is synthesized which has the effect of inhibiting the agglomeration, dissolution and shedding of alloy nanoparticles. The prepared alloy catalyst not only has a highly ordered core-shell structure which can effectively inhibit the dissolution of base metals, but also has better catalytic performance and durability than uncoated catalysts, truly achieving both high catalytic performance and long durability.
[0073] The present application also provides an alloy catalyst, which is prepared according to the preparation method of the alloy catalyst in the above embodiment.
[0074] See also Figure 2 The alloy catalyst includes a carrier and alloy particles 10 loaded on the carrier, the alloy particles 10 include a core 100, a first shell 200 and a second shell 300, the first shell 200 is coated on the surface of the core 100, the second shell 300 is coated on the surface of the first shell 200, the core 100 is an alloy, the first shell 200 is a platinum layer, and the second shell 300 is a carbon layer.
[0075] Optionally, the particle size of the alloy particles is 2.5 nm to 5 nm.
[0076] Optionally, the metal loading of the alloy catalyst is between 20% and 60%.
[0077] The alloy catalyst of the present application is an ultra-thin carbon layer coated ordered core-shell alloy catalyst, which can inhibit the agglomeration, dissolution and shedding of alloy nanoparticles. It not only has a highly ordered core-shell structure, which can effectively inhibit the dissolution of base metals, but also has better catalytic performance and durability than uncoated catalysts, truly achieving both high catalytic performance and long durability.
[0078] The following is a further detailed description of an alloy catalyst and a preparation method thereof of the present application in conjunction with embodiments.
[0079] Example 1
[0080] The present invention provides an alloy catalyst and a preparation method thereof, which comprises the following steps:
[0081] S1. Preparation of lyophilized material
[0082] First, cobalt nitrate and chloroplatinic acid are uniformly dispersed in water by ultrasonication at a molar ratio of cobalt element to platinum element of 3:1 to obtain a mixed solution, and then the mixed solution and Ketjen black are added to a stirring tank for stirring and mixing treatment. The mixing treatment time is 2 hours. After the mixing treatment is completed, it is transferred to a glass watch glass within 5 minutes for liquid nitrogen pre-freezing to obtain a pre-frozen material, and then the pre-frozen material is transferred to a freeze dryer for freezing for 24 hours to obtain a freeze-dried material.
[0083] S2. Preparation of initial alloy catalyst
[0084] The prepared lyophilized material was transferred to a porcelain boat and heat treated in a tubular furnace. Before the heat treatment, nitrogen was introduced into the tubular furnace at room temperature for 60 minutes to expel the air in the tubular furnace, and then hydrogen and nitrogen were introduced into the tubular furnace, and the volume ratio of hydrogen to nitrogen was 100mL:300mL. Then, the temperature was increased to 300°C at a heating rate of 5°C / min to 10°C / min, and the temperature was kept at 300°C for 3 hours to obtain an initial alloy catalyst, which was an alloy supported on a carbon carrier.
[0085] S3. Preparation of alloy catalyst
[0086] The prepared alloy loaded on the carbon carrier is oxidized in a tubular furnace by passing air at a heating rate of 5°C / min to 10°C / min, and the temperature is raised to 90°C, and kept at 90°C for 3 hours to obtain a first precursor, and then the first precursor is transferred to a porcelain boat and annealed in a tubular furnace. Before annealing, nitrogen is passed into the tubular furnace at room temperature for 60 minutes to exhaust the air in the tubular furnace, and then carbon monoxide and nitrogen are passed into the tubular furnace, and the volume ratio of carbon monoxide to nitrogen is 30mL:500mL, and then the temperature is raised to 700°C at a heating rate of 10°C / min to 50°C / min, and kept at 700°C for 3 hours to obtain an alloy catalyst, and the metal loading of the alloy catalyst is 50%.
[0087] Figure 3 is the TEM image of the alloy catalyst prepared in Example 1. Figure 3 It can be seen that the surface of the alloy nanoparticles is covered with an ultra-thin carbon shell, and the thickness of the ultra-thin carbon shell is 0.5nm.
[0088] Example 2
[0089] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Based on Embodiment 1, Embodiment 2 changes the volume ratio of carbon monoxide to nitrogen in the annealing treatment to 10 mL:500 mL, while other aspects remain unchanged.
[0090] Example 3
[0091] The examples of the present application provide an alloy catalyst and a preparation method thereof. Example 3 changes the volume ratio of carbon monoxide and nitrogen in the annealing treatment to 50 mL:500 mL on the basis of Example 1, while other aspects remain unchanged.
[0092] Example 4
[0093] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 4 is based on Embodiment 1, except that the annealing temperature in the annealing treatment is changed to 600° C., while other aspects remain unchanged.
[0094] Example 5
[0095] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 5 is based on Embodiment 1, except that the annealing temperature in the annealing treatment is changed to 800° C., while other aspects remain unchanged.
[0096] Example 6
[0097] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 6 changes the annealing temperature in the annealing treatment to 900° C. on the basis of Embodiment 1, while other aspects remain unchanged.
[0098] Example 7
[0099] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 7 changes the annealing time in the annealing treatment to 2 hours based on Embodiment 1, while other aspects remain unchanged.
[0100] Example 8
[0101] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 8 changes the annealing time in the annealing treatment to 5 hours on the basis of Embodiment 1, while other aspects remain unchanged.
[0102] Example 9
[0103] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 9 changes the oxidation temperature in the oxidation treatment to 120° C. on the basis of Embodiment 1, while other aspects remain unchanged.
[0104] Example 10
[0105] The embodiments of the present application provide an alloy catalyst and a preparation method thereof. Embodiment 9 changes the oxidation time in the oxidation treatment to 6 hours based on Embodiment 1, while other aspects remain unchanged.
[0106] Comparative Example 1
[0107] The comparative example of the present application provides an alloy catalyst and a preparation method thereof, which comprises the following steps:
[0108] S1. Preparation of lyophilized material
[0109] First, cobalt nitrate and chloroplatinic acid are uniformly dispersed in water by ultrasonication at a molar ratio of cobalt element to platinum element of 3:1 to obtain a mixed solution, and then the mixed solution and Ketjen black are added to a stirring tank for stirring and mixing treatment. The mixing treatment time is 2 hours. After the mixing treatment is completed, it is transferred to a glass watch glass within 5 minutes for liquid nitrogen pre-freezing to obtain a pre-frozen material, and then the pre-frozen material is transferred to a freeze dryer for freezing for 24 hours to obtain a freeze-dried material.
[0110] S2. Preparation of initial alloy catalyst
[0111] The prepared lyophilized material was transferred to a porcelain boat and heat treated in a tubular furnace. Before the heat treatment, nitrogen was introduced into the tubular furnace at room temperature for 60 minutes to expel the air in the tubular furnace, and then hydrogen and nitrogen were introduced into the tubular furnace, and the volume ratio of hydrogen to nitrogen was 100mL:300mL. Then, the temperature was increased to 300°C at a heating rate of 5°C / min to 10°C / min, and the temperature was kept at 300°C for 3 hours to obtain an initial alloy catalyst, which was an alloy supported on a carbon carrier.
[0112] S3. Preparation of alloy catalyst
[0113] The prepared alloy loaded on the carbon carrier is transferred to a porcelain boat and annealed in a tubular furnace. Before the annealing, nitrogen is introduced into the tubular furnace at room temperature for 60 minutes to exhaust the air in the tubular furnace, and then carbon monoxide and nitrogen are introduced into the tubular furnace, and the volume ratio of carbon monoxide to nitrogen is 30mL:500mL. Then, the temperature is increased to 700°C at a heating rate of 10°C / min to 50°C / min, and the temperature is kept at 700°C for 3 hours to obtain an alloy catalyst with a metal loading of 50%.
[0114] Comparative Example 2
[0115] The comparative example of the present application provides an alloy catalyst and a preparation method thereof, which comprises the following steps:
[0116] S1. Preparation of lyophilized material
[0117] First, cobalt nitrate and chloroplatinic acid are uniformly dispersed in water by ultrasonication at a molar ratio of cobalt element to platinum element of 3:1 to obtain a mixed solution, and then the mixed solution and Ketjen black are added to a stirring tank for stirring and mixing treatment. The mixing treatment time is 2 hours. After the mixing treatment is completed, it is transferred to a glass watch glass within 5 minutes for liquid nitrogen pre-freezing to obtain a pre-frozen material, and then the pre-frozen material is transferred to a freeze dryer for freezing for 24 hours to obtain a freeze-dried material.
[0118] S2. Preparation of initial alloy catalyst
[0119] The prepared lyophilized material was transferred to a porcelain boat and heat treated in a tubular furnace. Before the heat treatment, nitrogen was introduced into the tubular furnace at room temperature for 60 minutes to expel the air in the tubular furnace, and then hydrogen and nitrogen were introduced into the tubular furnace, and the volume ratio of hydrogen to nitrogen was 100mL:300mL. Then, the temperature was increased to 300°C at a heating rate of 5°C / min to 10°C / min, and the temperature was kept at 300°C for 3 hours to obtain an initial alloy catalyst, which was an alloy supported on a carbon carrier.
[0120] S3. Preparation of alloy catalyst
[0121] The prepared alloy loaded on the carbon carrier was transferred to a porcelain boat and annealed in a tubular furnace. Before the annealing, nitrogen was introduced into the tubular furnace at room temperature for 60 minutes to exhaust the air in the tubular furnace, and then nitrogen was introduced into the tubular furnace with a volume of 500 mL. The temperature was then increased to 700°C at a heating rate of 10°C / min to 50°C / min, and the alloy catalyst was prepared by keeping the temperature at 700°C for 3 hours. The metal loading of the alloy catalyst was 50%.
[0122] The process parameters of Examples 1 to 10 and Comparative Examples 1 to 2 are shown in Table 1.
[0123] Table 1 Process parameters of Examples 1 to 10 and Comparative Examples 1 to 2
[0124]
[0125]
[0126] Test Example 1
[0127] The alloy catalysts of Examples 1 to 10 and Comparative Examples 1 to 2 were taken to measure their order and particle size as well as their performance in the membrane electrode. The results are shown in Table 2 and Table 3. The XRD patterns of Example 1 and Comparative Example 2 are shown in Figure 4 shown.
[0128] The test method is as follows:
[0129] 1. Orderliness test
[0130] To calculate the degree of order of different platinum-cobalt alloy samples, we use the ratio of the intensity or integrated area of the superlattice reflection to the non-characteristic reflection as a quantitative assessment. For example, for PtCo, we use the ratio of the integrated area under the (110) plane to the sum of the areas under the (111), (200) and (002) planes, S(110) / (S(111)+S(200)+S(002)), as a quantitative assessment. For the 100% ordered intermetallic compound fct-PtCo (JCPDS: 65-8969), the value of S(110) / (S(111)+S(200)+S(002)) is 0.1677. Then the ratio of the actually calculated ratio S(110) / (S(111)+S(200)+S(002)) to the theoretical ratio of fct-PtCo is the corresponding degree of order of the catalyst. (DOI: 10.1038 / s41467-022-34037-7).
[0131] 2. Particle size test
[0132] The average particle size of 100 metal nanoparticles was obtained by HR-TEM testing.
[0133] 3. Performance test conditions of alloy catalysts in membrane electrode
[0134] Hydrogen (0.6L / min) was distributed to the anode and air (1.1L / min) was distributed to the cathode. The relative humidity of the anode was set to 30%, the humidity of the cathode was set to 55%, the anode inlet pressure was 90kpa, the cathode inlet pressure was 80kpa, and the stack temperature was 80°C. The maximum current was loaded and activated under constant current conditions for about 30 minutes under hydrogen and oxygen conditions, and then the cathode was switched to air. After the voltage stabilized for about 20 minutes, the membrane electrode performance was finally tested.
[0135] Table 2 Order and particle size of alloy catalysts of Examples 1 to 10 and Comparative Examples 1 to 2
[0136] project Order degree (%) Particle size (nm) Example 1 72 3.5 Example 2 54.4 4.2 Example 3 70.9 3.4 Example 4 41.8 3.3 Example 5 68.1 4.1 Example 6 61.3 5.2 Example 7 60.9 3.3 Example 8 73.2 3.8 Example 9 61.0 3.9 Example 10 64.7 3.8 Comparative Example 1 34.2 3.6 Comparative Example 2 24.9 4.9
[0137] Table 3 Performance of alloy catalysts in membrane electrode of Examples 1 to 10 and Comparative Examples 1 to 2
[0138]
[0139]
[0140] It can be seen from the above that the oxidation treatment and the thermal annealing temperature in Example 1 are appropriate, and the performance of the alloy catalyst obtained is better.
[0141] By comparing Example 2 with Example 1, it can be seen that the CO concentration in Example 2 is lower, the confinement effect on the alloy particles is weaker, and the electrochemical active area (ECSA) of the prepared alloy catalyst is lower, but due to the oxidation treatment, the final catalyst performance shows higher low-electrical density performance and poorer high-electrical density performance.
[0142] Comparison between Example 3 and Example 1 shows that the CO concentration in Example 3 is higher, which may result in the formation of an overly thick carbon shell that blocks the alloy active sites, and thus the performance of the obtained alloy catalyst is slightly worse than that in Example 1.
[0143] Comparison between Example 4 and Example 1 shows that the heat treatment temperature of Example 4 is lower, and the obtained alloy catalyst has a higher electrochemical active area (ECSA), but the ordering is insufficient, so its performance is slightly worse than that of Example 1.
[0144] Comparison between Examples 5 and 6 and Example 1 shows that the heat treatment temperatures of Examples 5 and 6 are higher, the electrochemical active area (ECSA) of the obtained alloy catalysts is reduced, and the performance is slightly reduced.
[0145] By comparing Example 7 with Example 1, it can be seen that the annealing time of Example 7 is shorter. Although the obtained catalyst has a smaller particle size and a higher electrochemical active area (ECSA), it is not sufficiently ordered, the catalyst activity is worse than that of Example 1, and the low electric density performance is reduced.
[0146] Comparison between Comparative Example 1 and Example 1 shows that Comparative Example 1 was not subjected to oxidation treatment. Although the alloy catalyst obtained had a higher electrochemical active area (ECSA), it was not sufficiently ordered, and its catalytic activity was worse than that of Example 1, and its low electric density performance decreased.
[0147] Comparison between Comparative Example 2 and Example 1 shows that Comparative Example 2 has no oxidation treatment and CO treatment, and the ordering and electrochemical active area (ECSA) of the prepared alloy catalyst are insufficient, and the overall performance is poor.
[0148] Test Example 2
[0149] The alloy catalysts of Examples 1 to 10 and Comparative Examples 1 to 2 were tested for long-term durability in membrane electrodes. The results are shown in Table 4.
[0150] Long-term durability test conditions of alloy catalysts in membrane electrodes:
[0151] Hydrogen (0.5L / min) was distributed to the anode and air (1L / min) was distributed to the cathode. The relative humidity of the anode was set to 25%, the humidity of the cathode was set to 50%, the anode stack pressure was 80kpa, the cathode stack pressure was 70kpa, and the stack temperature was 75°C. The battery was loaded to the maximum current and activated under hydrogen and oxygen conditions for about 30 minutes. Then the cathode was switched to air. After the voltage stabilized for about 15 minutes, the VI performance was finally tested.
[0152] Hydrogen (0.2L / min) was distributed to the anode and nitrogen (0.075L / min) was distributed to the cathode. The relative humidity of the cathode and anode was set to 100%, the cathode and anode inlet pressure was normal pressure, and the stack temperature was 80°C. A square wave cycle of 0.6V 3s and 0.95V 3s was performed. A catalyst aging test was performed for 3w cycles.
[0153] Table 4 Long-term durability test of alloy catalysts of Examples 1 to 10 and Comparative Examples 1 to 2 in membrane electrodes
[0154]
[0155]
[0156] It can be seen from the above that the alloy catalysts of Examples 1 to 10 all have relatively high catalyst resistance performance.
[0157] Comparison between Comparative Example 1 and Example 1 shows that the catalyst durability of the alloy catalyst prepared in Comparative Example 1 is worse than that in Example 1 because no oxidation treatment is performed.
[0158] Comparison of Comparative Example 2 with Comparative Example 1 and Example 1 shows that the catalyst durability of the alloy catalyst prepared in Comparative Example 2 without oxidation treatment and CO treatment is worse than that in Example 1 and also worse than that in Comparative Example 1.
[0159] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing an alloy catalyst, characterized in that: The preparation method of the alloy catalyst comprises: Placing the initial alloy catalyst in an atmosphere containing oxygen for oxidation treatment to obtain a first precursor, and then placing the first precursor in an atmosphere containing carbon monoxide for annealing treatment, wherein the annealing temperature is 650° C. to 900° C. and the annealing time is 2 h to 5 h, to obtain the alloy catalyst; The initial alloy catalyst includes a carrier and initial alloy particles supported on the carrier, wherein the initial alloy particles include platinum and a transition metal.
2. The method for preparing the alloy catalyst according to claim 1, characterized in that: The molar ratio of platinum to transition metal in the initial alloy particles is 1:3 to 5:1; and / or the carrier comprises a carbon carrier or an oxide carrier.
3. The method for preparing the alloy catalyst according to claim 1, characterized in that: The atmosphere of the annealing treatment includes carbon monoxide and an inert gas, and the volume ratio of carbon monoxide to the inert gas is 10 mL:200 mL to 100 mL:300 mL.
4. The method for preparing the alloy catalyst according to claim 1, characterized in that: The temperature of the oxidation treatment is 80° C. to 100° C., and the time of the oxidation treatment is 2 h to 5 h.
5. The method for preparing the alloy catalyst according to claim 1, characterized in that: The atmosphere for the oxidation treatment is air.
6. The method for preparing the alloy catalyst according to claim 1, characterized in that: The initial alloy catalyst can be prepared by the following method: The freeze-dried product is placed in an atmosphere containing hydrogen for heat treatment, wherein the heat treatment temperature is 200° C. to 400° C. and the heat treatment time is 2 h to 5 h; The lyophilizate includes a mixture of a transition metal precursor, a platinum precursor and the carrier.
7. The method for preparing the alloy catalyst according to claim 6, characterized in that: The lyophilized material is prepared by the following method: After the transition metal precursor, the platinum precursor and the carrier are mixed, they are transferred to a glass surface dish within 5 minutes for rapid pre-freezing to obtain a pre-frozen product, and then the pre-frozen product is transferred to a freeze dryer for freezing for 18 hours to 30 hours to obtain the freeze-dried product.
8. The method for preparing the alloy catalyst according to claim 6, characterized in that: The transition metal includes any one or more of cobalt, nickel, iron and manganese; and / or the platinum precursor includes any one or more of chloroplatinic acid, platinum acetylacetonate and potassium chloroplatinate.
9. An alloy catalyst, characterized in that: The alloy catalyst is prepared according to the method for preparing the alloy catalyst according to any one of claims 1 to 8.
10. The alloy catalyst according to claim 9, characterized in that: The alloy catalyst includes a carrier and alloy particles loaded on the carrier, the alloy particles include a core, a first shell and a second shell, the first shell is coated on the surface of the core, the second shell is coated on the surface of the first shell, the core is an alloy, the first shell is a platinum layer, and the second shell is a carbon layer.
Citation Information
Patent Citations
Preparation method of platinum-based octahedral catalyst
CN111048793A
Improved composition of a selective oxidation catalyst for use in fuel cells
CN1299523A
Electrode catalyst particle for fuel batteries, electrode catalyst for fuel batteries arranged by use thereof, electrolyte-electrode assembly, fuel battery, and methods for manufacturing catalyst particle and catalyst
JP2015035356A
Catalyst for anode of fuel cell, anode and fuel cell
JP2017042759A
Catalyst for fuel cell
JP2018181674A